ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TRANSFER PRICING PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - Limarjani, Sustinah; Ni’mah, Khairun (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this study was to analyze the effect of income tax, profitability, leverage and company size on transfer pricing in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The population of this study included 83 energy sector companies, using purposive sampling technique resulted in 28 samples, the research was conducted for 3 years of observation resulting in 84 data analyzed. The data in the study were obtained from secondary sources and data analysis was carried out using multiple linear regression with the help of SPSS version 26. The results of the research in the f statistical test revealed that together income tax, profitability, leverage and company size had an effect on transfer pricing. Meanwhile, partially in the t statistical test revealed that income tax has a positive effect on transfer pricing, while profitability has no effect on transfer pricing. Meanwhile, leverage and company size negatively affect transfer pricing. This research is expected to provide understanding and reference information related to the influence of various factors on transfer pricing.